Lean against the wind or float with the storm? Revisiting the monetary policy asset price nexus by means of a novel statistical identification approach - Helmut Herwartz; Simone Maxand; Hannes Rohloff (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
This paper revisits the monetary policy asset price nexus employing a novel identification approach for structural VARs in a framework of non-Gaussian independent shocks. This allows us to remain "agnostic" about the contemporaneous relations between the variables. We provide empirical evidence on the U.S. economy for monetary policy shocks and shocks originating from two asset markets: Equity and housing. Our results indicate that contractionary monetary policy shocks have a mildly negative impact on both asset prices. The effect is less pronounced for equity. Moreover, we find considerable differences in the speed of monetary policy transmission among both asset classes.
Keywords: C32; E44; E52; 330